Response A Trees Date palm Phoenix dactylifera L. For salt stress conditions - Hassanein M. Gabash; Mortada Shanan Awda; Al-Rabea’A, J.A.R (University of Thi-Qar Journal of agricultural research, 2024)
Degradation of agricultural land due to soil salinity and irrigation water is one of the major soil constraints that greatly hinders agricultural production and food security in any country and is one of the most difficult challenges at present, in addition to climate change and increasing frequency lonliness Phenomena Climate Extreme Especially Recurring droughts have attracted the attention of researchers to address them and develop possible solutions to address them by relying on the research aspect, which is of utmost importance, with the aim of improving soil resource capabilities and irrigation management by improving the quality and productivity of irrigation water in order to maintain the sustainability of the agricultural sector. The current review summarizes an explanation of how salt stress affects growth indicators in palm trees, which negatively and significantly affects the ability and production. Agricultural and thus disturbance and imbalance in providing the growing global demand, especially with the steady increase in population growth. Discusses the effect of soil salinity and irrigation water on plant pigments and some growth indicators and characteristics Physics For the fruits The result Furthermore, the article deals with determining the effect of salt stress on the mineral content of leaves and fruits. As significant indicators for assessing the severity and intensity of salt stress, it is therefore recommended to conduct more comprehensive studies on a larger scale, which will contribute to understanding these effects in developing strategies to reduce and minimize salt stress and its harmful effects on date palm cultivation.